Water quality and fish diversity in the Brantas River, East Java, Indonesia - Alfiah Hayati; Nureka Tiantono; Muhamad Fadhil Mirza; Iman Dary Supriyadi Putra; Muhamad Maulana Abdizen; Antien Rekyan Seta; Binti Mar`atus Solikha; Muhamad Hilman Fu'adil; Trisnadi Widyaleksono Catur Putranto; Mochamad Affandi; Rosmanida Rosmanida (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2017)
This research aimed to determine the water quality and fish diversity in Brantas river. Three station for sampling locations were in the upstream (one station on Karangkates reservoir) and downstream (two stations on the Surabaya and Jagir river). Water quality parameters were BOD, COD, DO, pH, temperature, and the levels of heavy metals (Pb, Cr, Cu, and Cd). Fish specimens was identified using fish identification book. The results of this research indicated that there was a difference in the water quality of upstream and downstream of the Brantas river. On the upstream, the source of pollution was mostly from fish catching, agriculture, and industrial activities. While on the downstream of the river it mostly dominated by industrial waste and domestic waste. The water quality in both stations had far exceeded the quality standards that was included in the polluted category. The concluded that Brantas river has been contaminated by waste (heavy metals), exceeded the water quality standard. The diversity of fish in the downstream (Surabaya river) has the highest diversity values, followed Jagir river and in the upstream (Karangkates reservoir) has the lowest value of diversity. Brantas river water was included in the category of moderate diversity.